WSPÓŁCZESNE ZNACZENIE I ROZUMIENIE RODZINY W POLSCE - Boguszewski, Rafał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The socio-cultural changes in the field of marriage and family related to the increasing number of divorces, postponing or avoiding decisions about marriage and procreation, as well as a significant increase in the number of informal relationships and the children in such families, inevitably leads to redefinition of the concept of family. Important question is how the contemporary Poles define the family, what roles family play nowadays and what are preferred and implemented models of family life in Poland? The article answers these questions based on the results of quantitative research carried out in recent years by the Public Opinion Research Center.